MANAJEMEN KEUANGAN DAN PEMASARAN DARING EFEKTIF, STRATEGI BANGKITKAN KEMBALI PEREKONOMIAN PAGUYUBAN UMKM BATIK JETIS SIDOARJO - Yanuar Nugroho; Maurisia Putri Permatasari; Izmi Dwira Eriani (Universitas Airlangga, 2021)
AbstractKampoeng Batik Jetis Sidoarjo has existed since 1,675 with the character of Sidoarjo's traditional hand-drawn batik which until now has been well preserved. It is named Kampoeng Batik Tulis because the majority of residents of Jetis sub-district, Sidoarjo sub-district are batik makers. During the economic crisis of the COVID-19, the efforts of SMEs in the Jetis Batik Community in developing business are not easy. Limited capital and uncertain market share are difficult problems for SMEs to deal with. The ability to manage the finances of SMEs business is very necessary for business performance and business continuity to anticipate the impact of the economic crisis. In addition, the SMEs of the Jetis Batik Community have always relied on outlet stores to market their products, resulting in a drastic drop in turnover due to social restrictions. This program is prepared to meet the need for increasing scientific knowledge and expertise that can support business continuity, especially SMEs, as well as increasing productivity and business profits that are run in the long term. This activity program will present professional speakers in related fields using knowledge sharing methods through lecture techniques, discussions, and mentoring practices in making management systems for operating business accounting records, business financial management, and marketing techniques for SMEs products. The target participants for this training are members of the UMKM of Batik Jetis, Sidoarjo Regency, who need special handling so that they can immediately rise from adversity, especially due to the impact of the Covid-19 pandemic economic crisis. This program is carried out in the form of training and mentoring activities for a total period of 6 months. There are several outcomes result from this activity, including increasing knowledge and insight in the field of operational management of business accounting records; increasing knowledge and insight in the field of business financial management; increasing ability and insight in the field of creative ideas in marketing SMEs products; increasing knowledge and insight in the field of online marketing techniques for SME products; increasing knowledge in the field of entrepreneurship; and improving the skills of members of the UMKM Batik Jetis.Keywords: Crisis, Economic, financial, MarketingAbstrakKampoeng Batik Jetis Sidoarjo telah eksis sejak tahun 1.675 dengan karakter batik tulis tradisional Sidoarjo yang hingga kini terpelihara dengan baik. Dinamakan Kampoeng Batik Tulis karena mayoritas warga kelurahan Jetis Kecamatan Sidoarjo adalah pembatik. Di masa krisis ekonomi pandemi covid-19 seperti sekarang ini upaya UMKM di Paguyuban Batik Jetis dalam pengembangan usaha tidaklah mudah. Keterbatasan modal dan pangsa pasar yang tidak menentu menjadi masalah yang sulit dihadapi oleh UMKM. Kemampuan mengelola keuangan pelaku usaha UMKM sangat diperlukan untuk kinerja usaha dan keberlangsungan usaha untuk mengantisipasi dampak krisis ekonomi. Ditambah lagi para pelaku UMKM Paguyuban Batik Jetis selama ini selalu mengandalkan toko outlet untuk memasarkan produk menjadikan omzet menjadi turun drastis akibat pembatasan sosial. Program ini disiapkan untuk memenuhi kebutuhan akan peningkatan wawasan keilmuan dan keahlian yang dapat mendukung keberlangsungan usaha, terutama UMKM, serta peningkatan produktivitas dan keuntungan usaha yang dijalankan dalam jangka panjang. Program kegiatan ini akan menghadirkan pembicara-pembicara yang profesional di bidang terkait dengan menggunakan metode sharing knowledge melalui teknik ceramah, diskusi, dan praktik pendampingan pembuatan sistem manajemen pengelolaan operasional pencatatan akuntansi usaha, pengelolaan keuangan usaha, dan teknik pemasaran produk UMKM. Target peserta pelatihan ini adalah anggota UMKM Paguyuban Batik Jetis Kabupaten Sidoarjo, yang membutuhkan penanganan khusus agar dapat segera bangkit dari keterpurukan khususnya akibat dampak krisis ekonomi pandemi Covid-19. Program ini dilakukan dalam bentuk kegiatan pelatihan dan pendampingan selama kurun waktu total 6 bulan. Adapun beberapa luaran yang akan dihasilkan dari kegiatan ini, antara lain peningkatan pengetahuan dan wawasan di bidang pengelolaan operasional pencatatan akuntansi usaha; peningkatan pengetahuan dan wawasan di bidang pengelolaan keuangan usaha; peningkatan kemampuan dan wawasan di bidang ide kreatif dalam memasarkan produk UMKM; peningkatan pengetahuan dan wawasan di bidang teknik pemasaran produk UMKM secara daring; peningkatan pengetahuan dan wawasan di bidang kewirausahaan; dan peningkatan keterampilan anggota UMKM Paguyuban Batik Jetis.Kata Kunci: Krisis, Ekonomi, Keuangan, Pemasaran